2015
DOI: 10.17576/3l-2015-2101-10
|View full text |Cite
|
Sign up to set email alerts
|

Topical Structure Analysis as an Assessment Tool in Student Academic Writing

Abstract: In an attempt to establish the validity of Topical Structure Analysis (TSA) as an assessment tool in student academic writing, this study applies TSA in both high-and low-rated comparison-and-contrast essays. Following Simpson's (2000) model, the study consists of two parts. The first part quantitatively describes the physical structure of freshman college students ' high-and low-quality comparison-and-contrast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…The study will complement previous studies interested in writing produced by L2 learners of English (Kim & Yoon 2014, Flores & Yin 2015. Practically, the present study can also benefit learners of English as a foreign language since it is able to enhance personal awareness related to how to use the amplifiers as well as the collocations correctly.…”
Section: Introductionmentioning
confidence: 56%
“…The study will complement previous studies interested in writing produced by L2 learners of English (Kim & Yoon 2014, Flores & Yin 2015. Practically, the present study can also benefit learners of English as a foreign language since it is able to enhance personal awareness related to how to use the amplifiers as well as the collocations correctly.…”
Section: Introductionmentioning
confidence: 56%
“…Another study by Flores and Kexiu (2015) provided conflicting results to Burneikaite and Zabiliute (2003). In their study, Flores and Kexiu applied TSA to analyse 29 comparison-and-contrast essays (15 high-quality and 14 low-quality) written by first-year ESL students at a private university in Manila.…”
Section: Relationships Between Types Of Topical Progression and Writing Qualitymentioning
confidence: 90%
“…Campbell (1998) designed an analytic rubric, called the Composition Analysis Rubric (CAR) to assess coherence in his students' writing. This CAR consists of three variables that were thought to be indicators of coherence: topical development, topical structure, and cohesive devices (Burneikaite & Zabiliute, 2003;Cerniglia, Medsker, & Connor, 1990;Flores & Kexiu, 2015;Knoch, 2007;Liangprayoon et al, 2013). The results of Campbell's (1998) study indicated that some of the components of the CAR such as topical structure analysis (TSA) are strong components of global coherence, and Campbell's (1998) study confirmed that it is possible to use topical structure analysis (TSA) to assess coherence in writing.…”
Section: Teaching Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Selection of description text because it is related to the description of an event through a process of observation and experience. Writing is an exploration and generative process to convey meanings (Flores, 2015). Cohesion in a writing lesson is usually based on socio-cultural aspects (Jay & Quinto, 2015).…”
Section: Introductionmentioning
confidence: 99%